Vaccination Coverage Against Human Papillomavirus (HPV) : A Study on Vaccination in the Municipality of Ananindeua, Brazil - , Camila Carvalho Do Vale, Maylane Cristina Barros Sousa, Bruna Rafaela Da Silva Sousa, Walter Lopes Neto, Felipe Valino Dos Santos, Gracileide Maia Corrêa, Perla Katheleen Valente Corrêa, Fabiola Caroline Nunes Dos Santos Ribeiro, Joyce Nathalia Carvalho Magalhães, Luiz Felipe Amorim Dos Santos, Patricia Lima Dos Santos Neves, Osvaldo Brito Da Costa Neto; et al. (Archives of Current Research International, 2024)
Objective: to analyze HPV vaccination coverage in the municipality of Ananindeua – Pará, from 2020 to 2024. Method: This is a quantitative study based on data from 2020 to 2024 collected by the Department of Informatics of the Unified System of Health (DATASUS), which allowed the analysis of HPV vaccination coverage. Results: The study revealed low adherence and significant fluctuations in HPV vaccination coverage, identifying as the main barriers the lack of information, the stigmatization of sexual transmission and the resistance of parents to vaccinating their children. Conclusion: The study showed a decline in HPV vaccination uptake from 2020 to 2024, threatening the WHO’s global goal of 90% by 2030. Key barriers include parental misinformation, vaccine myths, and a lack of trained professionals.